Effects of prior anterior cruciate ligament reconstruction on clinical outcomes associated with total knee arthroplasty: A protocol of retrospective analysis - Wang, Li-Zuo; Liu, Ai-Hua; Wen, De-Jian; Zhou, Yan-Tao (Medicine (Baltimore), 2020)
The argument on the clinical effects of previous anterior cruciate ligament (ACL) reconstruction on total knee arthroplasty (TKA) remains to be resolved. The aim of the current study was to compare operative and postoperative outcomes of patients undergoing TKA after ACL reconstruction with a matched cohort of control subjects having primary osteoarthritis and no history of ligament reconstruction. This study was performed and reported in accordance with the Strengthening the Reporting of Observational studies in Epidemiology checklist. The institutional review board approval of our hospital was obtained for the study. The ACL and control groups were matched 1:1 using a caliper width of 0.1 for the propensity score through nearest neighbor matching. Written informed consent was obtained from all subjects participating in the trial. The primary outcome measure was postoperative complications. Secondary outcome measures included operative time, tourniquet time, intraoperative complications, Oxford Knee Score, range of motion, and Western Ontario and McMaster Universities index. This study had limited inclusion and exclusion criteria and a well-controlled intervention. We hypothesized that prior ACL reconstruction had a negative impact on the operative and postoperative outcomes of TKA. This study protocol was registered in Research Registry (researchregistry5598).